1987
DOI: 10.1002/j.1460-2075.1987.tb02750.x
|View full text |Cite
|
Sign up to set email alerts
|

The ras-related ypt protein is an ubiquitous eukaryotic protein: isolation and sequence analysis of mouse cDNA clones highly homologous to the yeast YPT1 gene.

Abstract: The YPT1 gene of the yeast Saccharomyces cerevisiae codes for a guanine nucleotide‐binding protein which is essential for cell viability. Using as hybridization probe cloned yeast YPT1 gene sequences, we have isolated from cDNA libraries prepared from RNA of mouse F9 and C3H10T1/2 cells several overlapping cDNA clones with identical sequence in the regions of overlap. The cDNAs were derived from a gene, designated ypt1, which codes for a protein of 205 amino acids with 71% homology to the yeast YPT1 gene produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(66 citation statements)
references
References 39 publications
1
65
0
Order By: Relevance
“…Since S.pombe and S. cerevisiae are phylogenetically distantly related (Huysmans et al, 1983), these results suggest that the YPT family genes are widely conserved in eukaryotes. A gene that is 72 % homologous to Sc YPTI in amino acid sequence and can complement S. cerevisiae yptl has indeed been isolated from mouse and named yptl (Haubruck et al, 1987(Haubruck et al, , 1989. Genes encoding exactly the same amino acid sequence as mouse yptl have been isolated from a rat brain cDNA library (Touchot et al, 1987) and a human pheochromocytoma cDNA library (Zahraoui et al, 1989), and are named rabi and Hrabl respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since S.pombe and S. cerevisiae are phylogenetically distantly related (Huysmans et al, 1983), these results suggest that the YPT family genes are widely conserved in eukaryotes. A gene that is 72 % homologous to Sc YPTI in amino acid sequence and can complement S. cerevisiae yptl has indeed been isolated from mouse and named yptl (Haubruck et al, 1987(Haubruck et al, , 1989. Genes encoding exactly the same amino acid sequence as mouse yptl have been isolated from a rat brain cDNA library (Touchot et al, 1987) and a human pheochromocytoma cDNA library (Zahraoui et al, 1989), and are named rabi and Hrabl respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse RablA was first proposed to be a mammalian homolog of YPTlp on both the basis of its sequence similarity with YPTlp (>70% identity) and its ability to replace YPTlp in yeast when expressed at high levels (Haubruck et al, 1987(Haubruck et al, , 1989. Subsequent studies have confirmed the role of RablA in ER-to-Golgi transport in mammalian tissue-culture cells (Nuoffer et al, 1994).…”
Section: Cloning and Sequence Analysis Of Lerabla B And Cmentioning
confidence: 99%
“…By random sequencing of these cDNA libraries and computer anal- Fig. 2A shows a comparison of deduced amino acid sequences of ricl, yptm2 [lo], ara5 [6] and yptl [19]. ricl shares 83%, 81%, and 71% amino acid identity with yptm2, ara5 and yptl, respectively.…”
Section: Two Small Gtp-binding Protein Genes (Ricl and Ric2)mentioning
confidence: 99%
“…Fig. 2B shows a comparison of deduced amino acid sequences of ric2, ara2 [6], ypt3 [19] and rgpl [I 13. ric2 shares 79%, 68% and 58% amino acid identity with ara2, ypt3 and rgpl, respectively. The amino acid sequences of ric2 are conserved in four regions (shaded boxes in Fig.…”
Section: Dxxgmentioning
confidence: 99%
See 1 more Smart Citation